The effectiveness of nonstandard monetary policy measures: Evidence from survey data - Carlo Altavilla; Domenico Giannone (Federal Reserve Bank of New York, 2015)
We assess the perception of professional forecasters regarding the effectiveness of unconventional monetary policy measures announced by the U.S. Federal Reserve after the collapse of Lehman Brothers. Using survey data collected at the individual level, we analyze the change in forecasts of Treasury and corporate bond yields around the announcement dates of nonstandard monetary policy measures. We find that professional forecasters expect bond yields to drop significantly for at least one year after the announcement of accommodative policies.
Keywords: E58; E65; 330; Survey of Professional Forecasters; large-scale asset purchases; quantitative easing; Operation Twist; forward guidance; tapering